Treatment stability with V-bend bonded retainers versus vacuum-formed retainers: 3-year follow-up of a randomized clinical trial - Sant\'Anna, Gabriel Querobim (2023)
Introduction: To compare the clinical effectiveness regarding the capacity to maintain Treatment Stability, Survival Rates, Periodontal Health and Patients Perception of V-bend bonded retainers (BR) versus vacuum-formed retainers (VFR) after 36 months. Methods: Two experimental groups were compared after finalization of orthodontic treatment. Both groups received upper and lower retainers. The BR group with V-bend BRs bonded in the lingual surfaces of the anterior teeth and the VFR group received upper and lower VFRs right after fixed appliances removal. The patients were evaluated in one time-point: after 36 months (T4) and compared to previous study. At this time-point digital models were obtained and analyzed with the OrthoAnalyzerTM software. Treatment Stability was the primary outcome. Survival Rates, Periodontal Health and Patients Perception were the secondary outcome. Intergroup comparisons regarding stability outcomes were performed using Mann-Whitney U-tests (P < 0.05). The Kaplan-Meier survival plot and the log-rank test were employed to assess the survival rates. Results: The BR group included 20 patients (10 female, 10 male; mean age, 16.50 ± 3.13 years) and the VFR group comprised 20 patients (10 female, 10 male; mean age, 16.12 + 2.41 years). After 36 months BRs were more effective in to maintain the incisors alignment in the maxilla (P < 0.006) and in the mandible (P < 0.002) compared to the VFRs. No differences were noticed in the intercanine and intermolar widths, overjet and overbite. There were also no differences in the retainers survival rates in the maxillary and mandibular arches. Conclusions: BRs were more effective to maintain the incisors stability compared to VFRs after 36 months. Besides, VFRs retainers presented the same survival rates in both arches, different from the BRs retainers, whose failure was greater in the maxilla.